Critical Dscourse Analysis on The Issue of Environmentally and Socially Damaged Nickel Mining for the Benefit of Foreign Countries in The Media of Fajar Malut - Hi Saleh, Zulkifli; Ajwan, Alkadri (UIR PRESS, 2023)
The problem discussed in this study is a negative politeness strategy. The method used in this study is a qualitative descriptive method because it aims to describe and classify various negative politeness strategies in the KompasTV YouTube video about the talk show